Sustainable practices : ESG and green innovation effect on CVC’s firm value - Castro, Diogo Miguel Silva de (2024)
This dissertation investigates the relationship of ESG, green innovation and firm value, in the context of corporate venture capital. The research dives into sustainability and environment to contribute knowledge to investors, companies and market players, and to raise awareness over the importance corporations have on pressing forward sustainable practices to the industry. The research focus on a sample of 62 U.S. firms during a period of 21 years. Theoretical background analysis suggests a positive impact proportioned by ESG and green innovation on the financial performance of firms. The findings on this paper corroborate the conclusions of the body of literature. The results on ESG indicate companies with higher ESG score have improved firm value. Furthermore, green innovation as measured in both, quantity (Count) and quality (Citations) lead to improved firm value when the green metric increased. Moreover, the combined effect of the two variables has a positive effect on firm value. Additionally, the paper delves into the mediation role of green innovation between ESG and firm value, but the results display no mediation effect. The findings in this research put a spotlight on the importance of addressing sustainability and the impact companies benefit from recognizing and adjusting towards sustainable practices.